Analysis of the Science Literacy Competency Profile of High School Students on Limited Energy Sources - Agustya, Nabila Ella; Jauhariyah, Mukhayyarotin Niswati Rodliyatul (Universitas Hamzanwadi, 2023)
Learning in the 21st century requires students to have the ability to face the times. One of the essential skills that must be possessed is scientific literacy. Scientific literacy is using scientific knowledge to identify questions, acquire new knowledge, explain scientific phenomena, and draw conclusions based on scientific evidence. This research aims to describe the scientific literacy profile of high school students in the subject matter of limited energy sources. Three competency indicators refer to PISA 2018: a) Explaining phenomena scientifically, b) Evaluating and designing scientific investigations, and c) Interpreting data and evidence scientifically. This research uses a quantitative approach with a descriptive analysis method. The study was conducted in June 2023 in the Even Semester of the 2022/2023 Academic Year at a public high school in Surabaya. The population in this study was 60 students. The instrument used is a scientific literacy test developed with a valid category and a reliability value of 0.811. The results of this study were that students' scientific literacy competency profiles were obtained at 37% low, 33% sufficient, 18% high, and 12% very high. As for the results of the percentage of students' scientific literacy abilities based on scientific literacy competencies, the highest category in the first competency of 63%, namely explaining phenomena scientifically, while the second competency of 62%, namely evaluating and designing scientific investigations obtains a lower percentage than the first competence, and 56%, namely interpreting data and evidence scientifically, has the lowest result among the three scientific literacy competencies.